Effects of long-term Ailanthus altissima extract supplementation on fear, cognition and brain antioxidant levels - Hafiz Muhammad Abdur Rahman; Sana Javaid; Waseem Ashraf; Muhammad Fawad Rasool; Hammad Saleem; Salman Ali Khan; Zaheer Ul-Haq; Syed Muhammad Muneeb Anjum; Tanveer Ahmad; Faleh Alqahtani; Anees Ur Rehman; Imran Imran (Elsevier, 2023)
Introduction: Ailanthus altissima is an indigenous plant known for various remedial properties. The present study aimed to evaluate the neuroprotective potential of methanolic extract Ailanthus altissima (AA) bark as current scientific trend is searching plant for neurodegenerative diseases, worldwide. Methodology: In in-vitro experiments, the AA was analyzed for phenols, flavonoids, antioxidative and cholinesterase inhibitory properties with subsequent detailed characterization for secondary metabolites. The in-vivo neurological effects were evaluated in rats through behavioral assessment for anxiety and memory after chronic administration (28 days) of 50-200 mg/kg of AA. At the end of behavior studies, isolated brains were biochemically tested to determine antioxidant enzyme activity. Results: AA was found rich in phenols/flavonoids and active in radical scavenging with the presence of 13 secondary metabolites in UHPLC-MS analysis. The AA yielded anxiolytic effects dose-dependently in the open field, light/dark and elevated-plus maze tests as animals significantly (P < 0.05 vs control group) preferred open arena, illuminated zone and exposed arms of maze. Similarly, the animals treated with AA showed significant (P < 0.05 vs amnesic group) increase in spontaneous alternation, discrimination index in y-maze, novel object recognition tests. Further, AA.Cr treated rats showed noticeably shorter escape latencies in Morris water maze tests.In biochemical analysis, the dissected brains AA treated rats showed reduced levels of AChE and malondialdehyde with increased levels of first-line antioxidant enzymes i.e. glutathione peroxidase and superoxide dismutase. These observed biological effects might be attributed to phenols and flavonoids constituents owned by AA. -The in-silico studies showed thatconessine and lophirone J phytocompounds have good blood-brain barrier permeability and interaction with AChE. Conclusion: The outcomes of this study validate that bark of Ailanthus altissima might work as a source of bioactive phytochemicals of neuroprotective potential.